EFEK LARVASIDA EKSTRAK ETANOL DAUN MAHKOTA DEWA (Phaleria macrocarpa) TERHADAP LARVA Aedes aegypti - Hadiyan Adhli M; Suri Dwi Lesmana; Wiwik Rahayu W (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Dengue Hemorrhagic Fever ( DHF ) is a disease caused by type I, II , III and IV dengue virus which is transmitted by Aedes aegypti and Aedes albopictus mosquitos. The effort to control this dengue vector by chemical larvicides still have an adverse impact the population and causing vector’s resistance . Botanical larvacides produced from plants material can be used as an alternative to reduce these impacts . Mahkota Dewa ( Phaleria macrocarpa ) is one of the potential plants as a botanical larvicidal. The aim of this research was to determine the larvacides effect of Phaleria macrocarpa leaves ethanol extract against Aedes aegypti larvae. The design of this research is an experimental includes preliminary test and final test. The final test divided into 7 groups, consists of 0 ppm , 100 ppm , 300 ppm , 500 ppm , 600 ppm , 900 ppm , 1000 ppm. Each group contained 20 larvae in 100 ml extract solution with 3 repetitions. The regression Probit Analysis concluded that the LC50 has 545,3 ppm and LC90 has 859,9 ppm.Keywords: Larvacides effect, Phelaria macrocarpa, Aedes aegypti